A DECONSTRUCTION OF FRUSTRATION-AGGRESSION THEORY OF POLITICAL VIOLENCE IN NIGERIA - Etim, Frank; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2023)
The work set out to deconstruct and reconstruct Ted Roberts Gurr’s (1970) theory of relative deprivation, frustration-aggression as contained in his work ‘Why Men Rebel’ (1970). The study used descriptive research design and evaluated the capacity of the theory, which was created to explain political violence in Africa and Asia in the colonial era, to also explicate why intense relative deprivation, frustration and aggression arising from the avalanche of poor governance in postcolonial African states such as Nigeria and many others, have not culminated into political violence and rebellion. The study presented numerous data obtained through observation and analysis of events in Nigeria, Africa and case-studies of American, French, English and Russian rebellions and distilled qualitative data which indicated lack of association between the variables. The application of the study design revealed first the state as the source of relative deprivation, frustration and aggressions of the citizenry when they are denied access to public values, which they feel entitled to. Secondly, it further discovered that there are no direct correlations between relative deprivation, frustration and aggression as initially conveyed by the theory since 1970. Furthermore, it exposed that there is an intervening variables identified as ‘Social Movements’ or ‘Civil Society Organizations (CSOs), which harness relative deprivation, intense frustration and aggressions from the sufferers and convert them to other set-of-action, which may not be political violence and rebellions but could be advocacy towards the expansion of the mechanism for supply of public good or values and to make it accessible to many as a means of addressing relative deprivation. The study concluded in the light of its findings, that the initial theory requires deconstruction and reconstruction to include ‘Social Movement’ as a principal component. It is only then that it could be applied in the analysis of issues in postcolonial African and Asian states